2006
DOI: 10.1002/nme.1685
|View full text |Cite
|
Sign up to set email alerts
|

Fixed-point convergence of modular, steady-state heat transfer models coupling multiple scales and phenomena for melt–crystal growth

Abstract: SUMMARYA block Gauss-Seidel iteration procedure is employed to couple two independent heat transfer codes representing different scales and phenomena in a melt-crystal growth system via shared domain boundaries. In general, such strategies are attractive because of their simplicity for solving problems that may be represented by linking, via shared boundary conditions, existing codes using a modular design. However, these approaches often meet with limited success due to convergence difficulties associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…The analysis employed here represents another step toward a model that more faithfully depicts the details of heat transfer in technically realistic furnaces. We believe that the next advance will effectively couple these two models with their respective strengths using algorithms that are currently under development [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis employed here represents another step toward a model that more faithfully depicts the details of heat transfer in technically realistic furnaces. We believe that the next advance will effectively couple these two models with their respective strengths using algorithms that are currently under development [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…If one step of each solver is taken withx ¼ x ðkÞ andỹ ¼ y ðkÞ , one iteration of the well-known Jacobi method is obtained. For the iterations used here and in our prior efforts [5][6][7][8], a block form of the Gauss-Seidel method is obtained by settingỹ ¼ y ðkÞ , solving for x ðkþ1Þ , then settingx ¼ x ðkþ1Þ to solve for y ðkþ1Þ . Hence, the BGS method consists of sequentially solving each model, rewriting Eqs.…”
Section: The Block Gauss-seidel (Bgs) Methodsmentioning
confidence: 99%
“…Pandy and co-workers [5,7] found that block Gauss-Seidel iteration performed poorly for this problem, often failing to converge at all. Derby et al [8] showed that under-relaxed BGS iterations were equally ineffective applied to this same problem.…”
Section: One-dimensional Heat Transfer Examplementioning
confidence: 98%
See 2 more Smart Citations